The direct effect of the World Trade Organization and the challenge for Brazilian courts (Revista do Tribunal Regional Federal da 3ª Região, 2017)
This paper analyses the relevant role of the Brazilian courts in ensuring the so called direct effect to WTO norms within the Brazilian legal system, at risk of, not doing so, (i) violating constitutional and legal rights associated with the right to access to the Judiciary and the duty to pay damages; and also (ii) impairing the effectiveness of the international obligations assumed by Brazil.
Keywords: WTO. Direct effect. Constitutional rights. Treaty effectiveness.; WTO; direct effect; constitutional rights; treat effectiveness